Hereditary Haemorrhagic Telangiectasia: an Unusual Cause for a Quiescent Pulmonary Nodule - Kumanan, T.; Sobika, S.; Suganthan, N.; Sriluxayini, M.; Gerald, S. (Sri Lanka College of Internal Medicine, 2026)
Hereditary haemorrhagic telangiectasia (HHT) is a rare autosomal dominant disorder with mucocutaneous telangiectasias and arteriovenous malformations (AVM). We report an asymptomatic patient with a pulmonary AVM (PAVM) found on routine imaging. He later disclosed recurrent childhood epistaxis and a family history suggestive of HHT. Imaging studies confirmed a large PAVM without other organ involvement. Early diagnosis and transcatheter embolisation helped prevent severe complications like stroke and haemorrhage. This case highlights the importance of exclusion of HHT as an important cause of an unexplained pulmonary shadow.
Keywords: Hereditary haemorrhagic telangiectasia; Pulmonary arteriovenous malformation; Curaçao criteria; Bubble echocardiogram